Training students at small & medium sized colleges in information literacy. - Primary Research Group ([New York] : Primary Research Group, 2013)
Librarians from sixteen small and medium sized colleges discuss their information literacy efforts, pointing out what works and does not work for them, trends in encouraging faculty buy in, use of tutorials and various forms of faculty and student outreach, technology and learning space design issues, and many other facets of information literacy education. The emphasis is on plans and best practices. --from publisher description.
Schenectady Community College -- Rollins College -- Pikes Peak Community College -- Providence College -- River Parishes Community College -- Embry-Riddle Aeronautical University -- Chattanooga State Community College -- Northeast Community College -- Lebanon Valley College -- Middlesex Community College -- Oberlin College -- Massasoit Community College -- Cecil College -- Marlboro College -- Genesee Community College -- Ottawa University.
Publisher location from publisher website.
Keywords: Information literacy -- Study and teaching (Higher) -- Case studies; Instructional systems -- Design -- Case studies; Information literacy -- Study and teaching (Higher); Instructional systems -- Design; Case studies; Case studies